Heritage for sustainable peace: the politics of contested histories and the Nanjing controversy at UNESCO - Huttunen, Miia (Frontiers in Political Science, 2024)
This article explores the politics of heritage of the 2015 Sino-Japanese confrontation resulting from the controversial inclusion of the “Documents of Nanjing Massacre” in UNESCO's Memory of the World Register, which promotes the preservation of archival documents as humanity's common heritage. Through an analysis of the Chinese nomination form proposing the inclusion of the documents in the register and the Japanese response to it, reflected against the principles of the register, this article examines how the seemingly apolitical and universal understanding of heritage and its links with sustainable peace proposed by organizations such as UNESCO fails to hold its ground when linked to the interests of a nation that claims ownership of it. Through an exploration of the Nanjing debate as a point of friction in the interplay of international ideals and national interests, it makes a case for an understanding of the interaction between the supranational and the national as a two-way street through the example of UNESCO's somewhat peculiar understanding of sustainable peace and its exploitation for political purposes. The article concludes that the idealistic effort to preserve archival heritage and to increase recognition of its significance seems to have become overshadowed by the MoW register's unintended facilitation of competing nationalistic narratives, leaving the door open for the exploitation of the register for purposes that contradict the very principles it was founded upon. Thus, while this case surfaces practical issues with the adoption of UNESCO's “heritage for sustainable peace” agenda seriously calling into question the realizability of such an idea, the mere fact that both China and Japan sought to seek ruling on their bilateral dispute through UNESCO implies a display of faith in the organization and its mission.